Influence of gas-dynamic parameters of the heat carrier on the efficiency of drying peas in rotary dryers with a fluidized bed - Yakobchuk, Roman; Lementar, Sviatoslav (My University, 2020)
Introduction. The aim of the research is determination the influence of gas-dynamic parameters of heat carrier movement in the chamber of a rotary drying unit with a fluidized bed on the efficiency of the peas drying process. Materials and methods. The research was carried out on an experimental drying unit with a conical element installed in the drying chamber, and with the help of 3D models of drying units. The simulation of the heat carrier movement was performed using CFD methods, followed by verification in a pilot plant. Results and discussion. It is established that the heat carrier speed in the drying chamber without a conical element is in the recommended limits (1.8–2 m/s) only in the range from 0 to 0.7 m in the height of the chamber. The zone from 0.7 to 1.2 m is used less efficiently, because the velocity of the heat carrier is in the range of 1.65–1.8 m/s. The reason for this is that when the heat carrier passes through the wet product, its temperature decreases, it leads to decreasing of heat carrier volume. This causes the destruction of the constant mode of heat carrier and consequently reducing of the intensity of drying of the product. In the drying unit with a conical element, the stabilization of the heat carrier speed is achieved within the recommended (1.8–2 m/s) limits along the entire height of the drying zone, which provides a constant height of the fluidized bed of product in the drying chamber. This creates the conditions for a higher intensity of drying the material and improves the quality of the dried product, because it does not stay for a long time in the high temperature zone. It is found out that with heat carrier speed increasing over 2 m/s there is a decrease in the efficiency of its potential. Thus at an initial speed of 2 m/s and an initial temperature of 100 C, its final temperature is about 55 C, which coincides with drying regulations for installations of this type. While increasing speed up to 2.2 and 2.4 m/s there is final temperature increasing of the heat carrier up to 58 and 60 C and as a result it reduces the efficiency of this installation. Conclusions. This research allows to determine the influence of the installation of a conical element in the drying chamber on the speed of the of heat carrier and its pressure in the drying zone, as well as the influence of the speed of the drying agent on its temperature in this zone.
Keywords: drying; peas; rotory; dryer; fluidization; кафедра технологічного обладнання та комп’ютерних технологій проектування